2013
DOI: 10.1080/14616734.2013.782649
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent attachment security, family functioning, and suicide attempts

Abstract: Theories of suicidal behavior suggest that the desire to die can arise from disruption of interpersonal relationships. Suicide research has typically studied this from the individual's perspective of the quality/frequency of their social interactions; however, the field of attachment may offer another perspective on understanding an individual’s social patterns and suicide risk. This study examined attachment along with broader family functioning (family adaptability and cohesion) among 236 adolescent psychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 64 publications
12
48
0
8
Order By: Relevance
“…However, few studies have utilized clinical samples (Joiner et al 2009) or specifically adolescent clinical samples (exceptions are Czyz et al 2014;Klonsky et al 2013;Liu et al 2014;Nock et al 2006;Prinstein et al 2008;Sheftall et al 2013). Relative to studies on acquired capability for suicide, there are fewer studies focusing on thwarted belongingness and perceived burdensomeness with adolescent clinical samples in the IPTS literature.…”
Section: Shortcomings In Literature Guiding This Studymentioning
confidence: 91%
See 1 more Smart Citation
“…However, few studies have utilized clinical samples (Joiner et al 2009) or specifically adolescent clinical samples (exceptions are Czyz et al 2014;Klonsky et al 2013;Liu et al 2014;Nock et al 2006;Prinstein et al 2008;Sheftall et al 2013). Relative to studies on acquired capability for suicide, there are fewer studies focusing on thwarted belongingness and perceived burdensomeness with adolescent clinical samples in the IPTS literature.…”
Section: Shortcomings In Literature Guiding This Studymentioning
confidence: 91%
“…Longitudinally, NSSI and history of suicide attempt (both indicators of acquired capability for suicide) demonstrated associations with post-discharge suicide attempt in an adolescent psychiatric inpatient sample . Indicators of thwarted belongingness such as paternal attachment, family cohesion, and family adaptability distinguished between those with and without lifetime history of suicide attempt in a sample of adolescents with a history of inpatient psychiatric care (Sheftall et al 2013).…”
Section: Shortcomings In Literature Guiding This Studymentioning
confidence: 99%
“…More recently, Sheftall et al (2013) examined the attachment patterns along with broader family functioning (family adaptability and cohesion) in a sample of 236 adolescent psychiatric inpatients with (n=111) and without (n=125) history of suicide attempts. Compared to those without suicide attempts, adolescent attempters had lower levels of self-reported maternal and paternal attachment, and lower familial adaptability and cohesion.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, research suggests that less flexible and cohesive families may not be able to adequately meet the adolescent's demands and needs for change within the family system, which may contribute to problematic behaviour [22]. For example, it has been found that adolescent perceptions of cohesion and flexibility in the family are significant predictors of suicide attempts [23]. Childhood depression has also been associated with disengaged family systems, marked by inadequate closeness and support [24].…”
Section: Introductionmentioning
confidence: 99%